Influence of the natural hormonal milieu on brain and behavior in women who smoke cigarettes: Rationale and methodology - Wetherill, Reagan R. (Contemp Clin Trials Commun, 2021)
Women experience more severe health consequences from smoking, have greater difficulty quitting, and respond less favorably to nicotine replacement therapy than men. The influence of fluctuating ovarian hormones, specifically estradiol (E) and progesterone (P), on brain and behavioral responses during exposure to smoking reminders (i.e., cues) may be a contributing factor. Results from our laboratory suggest that women in the late follicular phase of their menstrual cycle (MC) have enhanced smoking cue (SC) vulnerabilities and reduced functional connectivity in neurocircuitry underlying cognitive control, potentially placing them at greater risk for continued smoking and relapse. The primary aim of this study is to examine and link hormonal status with brain and behavioral responses to SCs over the course of three monthly MCs in naturally cycling women who are chronic cigarette smokers. This longitudinal, counterbalanced study collects brain and behavioral responses to SCs at three time points during a woman's MC. Participants complete psychological and physical examinations, biochemical hormonal verification visits, and at least three laboratory/neuroimaging scan visits. The scan visits include a 10-min SC task during blood oxygen level-dependent (BOLD) data acquisition and are timed to occur during the early follicular phase (low E and P), late follicular phase (high E, unopposed by P), and mid-luteal phase (high P, high E). The primary outcomes include brain responses to SCs (compared to non-SCs), subjective craving, E and P hormone levels, and behavioral responses to SCs. This study addresses a critical gap in our knowledge: namely, the impact of the natural hormonal milieu on brain and behavioral responses to SCs, a powerful relapse trigger. Additionally, this study will provide a roadmap for human sex differences researchers who are obliged to consider the often confounding cyclic hormonal fluctuations of women.